2013
DOI: 10.2527/jas.2013-6694
|View full text |Cite
|
Sign up to set email alerts
|

Variance components of aggressive behavior in genetically highly connected Pietrain populations kept under two different housing conditions1

Abstract: Mixing of unfamiliar pigs is a standard management procedure in commercial pig production and is often associated with a period of intense and physically damaging aggression. Aggression is considered a problem for animal welfare and production. The objective of the present paper was to investigate the genetic background of aggressive behavior traits at mixing of unfamiliar gilts under 2 different housing conditions. Therefore, a total of 543 purebred Pietrain gilts, from 2 nucleus farms (farm A: n = 302; farm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…The heritabilities ranged from h 2 = 0.22 ± 0.07 [24] to h 2 = 0.43 ± 0.04 [39]. However, in the present study heritabilities for skin lesion scores were lower (LS1: h 2 = 0.14 ± 0.06; LS2: h 2 = 0.12 ± 0.07) and within the range of results found for direct observations of aggressive behaviour (attacks: h 2 = 0.11 ± 0.07 to h 2 = 0.29 ± 0.13 / reciprocal fights h 2 = 0.04 ± 0.07 to h 2 = 0.33 ± 0.07, [40]). Earlier results suggested that lesion scores recorded shortly after mixing mostly reflect the number of attacks received, but not of being an initiator of aggressive interactions [25].…”
Section: Discussionsupporting
confidence: 81%
“…The heritabilities ranged from h 2 = 0.22 ± 0.07 [24] to h 2 = 0.43 ± 0.04 [39]. However, in the present study heritabilities for skin lesion scores were lower (LS1: h 2 = 0.14 ± 0.06; LS2: h 2 = 0.12 ± 0.07) and within the range of results found for direct observations of aggressive behaviour (attacks: h 2 = 0.11 ± 0.07 to h 2 = 0.29 ± 0.13 / reciprocal fights h 2 = 0.04 ± 0.07 to h 2 = 0.33 ± 0.07, [40]). Earlier results suggested that lesion scores recorded shortly after mixing mostly reflect the number of attacks received, but not of being an initiator of aggressive interactions [25].…”
Section: Discussionsupporting
confidence: 81%
“…The genetic correlation fell into range with genetic correlations between reciprocal aggression and the delivery of non-reciprocal aggression reported in other studies (Turner et al, 2008;D'Eath et al, 2009;Appel et al, 2013). A high positive genetic correlation was also found between SEPD1 and SEPD10, which indicates that these behaviour traits assessed at different points in time measured the same dimension of personality and therefore have a similar genetic background.…”
Section: Correlations Of the Behavioural Traitssupporting
confidence: 71%
“…All agonistic encounters shown by the newly mixed gilts were recorded (adapted from Hellbrügge, 2007 and as described in Appel et al, 2013). Aggressive behaviour was subdivided into aggressive attacks (i.e.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations